Cu Nanostructures for Enhanced Heat Transferin Micro Systems (University of Thi-Qar Journal for Engineering Sciences, 2017)
Vertically aligned copper (Cu) nanorod arrays fabricated by glancing angle deposition (GLAD) technique was used to study the heat transfer by natural convection in micro systems. These nanorods were deposited on Cu thin film surface, which was coated on Si (100) wafer substrates. For comparison, planar Cu thin film samples were also produced by normal incidence deposition. This study focuses on investigating experimentally the heat transfer by natural convection from the sample(nanostructured plate) to the surrounding air. Newton's law of cooling has been utilized to calculate the free-convection heat transfer coefficient for Cu nanorods as well as Cu thin film. Compered to Cu thin film samples, it has been found that the heat transfer coefficient values of Cu nanorods are higher due to the enhanced heat transfer-surface area, which causes a significant reduction in thermal resistance. These nanostructured surfaces offer an effective method of device cooling such as for small electronic devices, micro-reactors and air conditioning.